Availability and readiness of public health facilities to provide differentiated service delivery models for HIV treatment in Zambia: implications for better treatment outcomes - Kaonga, Patrick; Sampa, Mutale; Musukuma, Mwiche; Mulawa, Mulanda Joseph; Mulavu, Mataanana; Sitali, Doreen; Moonga, Given; Mweemba, Oliver; Matenga, Tulani Francis; Zyambo, Cosmas; Hamoonga, Twaambo; Phiri, Henry; et al. (Frontiers in Public Health, 2024)
BackgroundThere is persistent pressure on countries with a high burden of HIV infection to reach desired targets for HIV treatment outcomes. This has led to moving from the “one-size-fits-all” model to differentiated service delivery (DSD) models, which are meant to be more patient-centered and efficient but without compromising on the quality of patient care. However, for DSD models to be efficient, facilities should have indicators of HIV services available and ready to provide the DSD models. We aimed to assess the availability of HIV service indicators and the readiness of facilities to provide DSD models for HIV treatment in selected public health facilities in Zambia.MethodsWe conducted a nationwide cross-sectional survey among public health facilities in Zambia that provide antiretroviral therapy (ART) services. We used an interviewer-administered questionnaire based on a World Health Organization (WHO) Service Availability Readiness Assessment (SARA) tool to assess the availability of HIV service indicators and the readiness of facilities to implement DSD models for HIV treatment. Availability and readiness were considered latent constructs, and therefore, we used structural equation modeling (SEM) to determine the correlations between them and their respective indicators.ResultsOf 60 public health ART facilities, the overall availability of HIV service indicators was 80.0% (48/60), and readiness to provide the DSD models was 81.7% (48/60). However, only 48 and 39% of the facilities had all indicators of availability and readiness, respectively. Retention in care for HIV multidisciplinary teams was more likely to occur in urban areas than in rural areas. SEM showed that the standardized estimate between availability and readiness was significantly and positively correlated (r = 0.73, p < 0.0001). In addition, both availability and readiness were significantly and positively correlated with most of their respective indicators.ConclusionAlthough most facilities had available HIV service indicators and were ready to provide DSD models, most facilities did not have all indicators of availability and readiness. In addition, there were differences between rural and urban facilities in some indicators. There is a need for persistent and heightened efforts meant to implement DSD in HIV treatment, especially in rural areas to accelerate reaching the desired HIV treatment outcomes.